2015
DOI: 10.1007/s00500-015-1925-9
|View full text |Cite
|
Sign up to set email alerts
|

Using random forest and decision tree models for a new vehicle prediction approach in computational toxicology

Abstract: Drug vehicles are chemical carriers that provide beneficial aid to the drugs they bear. Taking advantage of their favourable properties can potentially allow the safer use of drugs that are considered highly toxic. A means for vehicle selection without experimental trial would therefore be of benefit in saving time and money for the industry. Although machine learning is increasingly used in predictive toxicology, to our knowledge there is no reported work in using machine learning techniques to model drug-veh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Similar to kNN algorithms, it is also used to for classification and to predict regression [80]. Compared to DTs, it is impossible that RF over-fits the data, and the RF has been used for bioactivity data classification [81], toxicity modeling [82], and drug target prediction [83], etc. Wang et al [84] used the RF approach to model the binding affinity of protein-ligand on 170 HIV-1 proteases complexes, 110 trypsin complexes, and 126 carbonic anhydrase complexes, which demonstrated that individual representation and model construction for each protein family is a more reasonable way in predicting the affinity of one particular protein family.…”
Section: Classical Qsar Methodsmentioning
confidence: 99%
“…Similar to kNN algorithms, it is also used to for classification and to predict regression [80]. Compared to DTs, it is impossible that RF over-fits the data, and the RF has been used for bioactivity data classification [81], toxicity modeling [82], and drug target prediction [83], etc. Wang et al [84] used the RF approach to model the binding affinity of protein-ligand on 170 HIV-1 proteases complexes, 110 trypsin complexes, and 126 carbonic anhydrase complexes, which demonstrated that individual representation and model construction for each protein family is a more reasonable way in predicting the affinity of one particular protein family.…”
Section: Classical Qsar Methodsmentioning
confidence: 99%
“…Scholars explore the correlation between the capacity utilization rate and the market supply of online ride-hailing and traditional taxi services, respectively [14]. They also analyze diverse service modes, service functions, price differences, and service profits in different forms of business [15][16][17][18]. Others investigate the effect of market mechanism on resource distribution [19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A subset of the training dataset (local set) is chosen to grow individual trees, with the remaining samples used to estimate the goodness of fit. Trees are grown by splitting the local set at each node according to the value of a random variable sampled independently from a subset of variables [26].…”
Section: Random Forestmentioning
confidence: 99%